Element accumulation capacity of Vaccinium myrtillus from Montenegro: Comparison of element contents in water and ethanol extracts of bilberry plant parts - Brašanac Vukanović, Snežana; Tadić, Vanja M.; Blagojević, Nada; Vukašinović Pešić, Vesna; Đurđić, Slađana; Stanković, Milica; Mutić, Jelena (Archives of Biological Sciences, 2019)
Paper description: Bilberry (Vaccinium myrtillus L., Ericaceae) and its extracts are used in traditional medicine. While research has focused on the health benefits of plant flavonoids, the element content is of potentialy great importance. This study provides information on which part of the bilberry (roots, stems, leaves or fruits) accumulates which elements and on how the metals taken up from the soil might be translocated from the roots to the above-ground parts of the plant. This study provides new findings on element distribution in bilberry and gives insight into the effect of the method of bilberry extract preparation on the element content. Abstract: Bilberry (Vaccinium myrtillus L., Ericaceae) is a rich source of different mineral elements that are important as essential trace elements, or that can be potentially toxic, depending on their concentration. The contents of sixteen elements: the major (Al, Ca, Fe, K and Mg) and trace elements (As, Ba, Cd, Co, Cu, Cr, Mn, Ni, Pb, Sr and Zn) in roots, stems, leaves and fruits of bilberry and the corresponding soil substrate were determined in order to investigate element mobility and availability in soil. Soil was subjected to sequential extraction procedure as proposed by the Community Bureau of Reference in order to fractionate acid-soluble/exchangeable, reducible, oxidizable and residual fractions. Analysis of water and ethanol extracts of bilberry aerial parts revealed a significant transfer of elements during the extraction procedure, with corresponding extraction coefficient values of up to 95.12%. Results showed that bilberry fruits could serve as a good dietary source of essential elements for humans, especially Mn and Cu. https://doi.org/10.2298/ABS181004056B Received: October 4, 2018; Revised: November 28, 2018; Accepted: November 30, 2018; Published online: December 14, 2018 How to cite this article: Brašanac-Vukanović S, Tadić VM, Blagojević N, Vukašinović-Pešić V, Đurđić S, Stanković M, Mutić J. Element accumulation capacity of Vaccinium myrtillus from Montenegro: Comparison of element contents in water and ethanol extracts of bilberry plant parts. Arch Biol Sci. 2019;71(1):145-57.